Modelování kvality ovzduší pomocí Kohonenových samoorganizujících se map - Olej, Vladimír; Hájek, Petr; Křupka Jiří; Obršálová, Ilona (Univerzita Pardubice, 2007)
The paper presents a design of parameters for air quality modelling and the classification of districts into classes according to their pollution. Further, it presents a model design, data pre-processing, the designs of various structures of Kohonen’s Self-organizing Feature Maps (unsupervised methods), the clustering by K-means algorithm and the classification.
Keywords: air quality; Modelling; Kohonen’s self-organizing feature maps; K-means algorithm; Classification